Labor force pluralism as a condition of István Mészáros’ socialist strategy - Firmiano, Frederico Daia (Universidade de São Paulo | Escola de Comunicações e Artes, 2018)
Since its modern historical constitution, the labor forces reached some important achievements along the concession margins of the capital, still in their phase of historical ascension. However, its main cornerstone, because they belong to the domain of the mystical institutional circle of the relationship between political State and civil society, have never been able to make the dream of the gradual construction of socialism comes true. Nowadays, when the structural crisis of the capital penetrates all domains and levels of social reproduction throughout virtually the entire planet, labor is driven to rebuild and renew itself in the form of an extra-parliamentary movement that rejects all structural determinations of the capital in the elaboration of an offensive socialist strategy as opposed to the historically defensive forms formerly assumed. This is what István Mészáros proposes in his monumental work, Beyond Capital: Toward a Theory of Transition. Within the limits of this manuscript, I try to explain the complex articulation between the structural crisis of the capital and the historical needs of the socialist offensive, focusing on what, for our Hungarian philosopher, is one of the major challenges of contemporary Marxist theory: the construction of pluralism as condition of socialist strategy.